Pleistocene megafauna coprolite analysis: inferences about dietary habits and vegetation in a highland ecosystem of South America - Nadia J. Velázquez; M. Eugenia Mosca Torres; Romina S. Petrigh; M. Laura Benvenuto; M. Fernanda Rodríguez; Federico M. Bobillo; Lidia S. Burry; Jorge G. Martínez; Carlos A. Aschero (Quaternary Science Reviews, 2026)

Pesticide removal by fluvial biofilms in lowland streams under different land uses and agricultural seasons - M. A. Mujica; E. De Gerónimo; A. Mosca; S. L. Fanelli; A. H. Paracampo; J. Cochero (International Journal of Environmental Science and Technology, 2026)

Genome resources of Pseudomonas sp. CFBP 5748 and Pseudomonas sp. CFBP 5750, fluorescent pseudomonads associated with tomato pith necrosis (FPTPN), clarify their position within the P. corrugata phylogenetic subgroup - G. Dimaria; D. Nicotra; A. Mosca; M. Fischer-Le Saux; P. Portier; V. Catara (Journal of Plant Pathology, 2026)

Insights into chlorination-induced degradation of sulfonylurea herbicides: Unraveling kinetics and intermediates during water treatment - Eduardo De Gerónimo; Agustín Mosca; Franco M. Cabrerizo; Ronald Vargas (Water Research, 2025)

Efficacy and innocuity of lotilaner in the treatment of otodectic mange in ferrets - M. Legain; A. Idee; D. Mardini; M. Rene-Martellet; M. Mosca; D. Pin (Veterinary Parasitology, 2024)

Techno-environmental and economic assessment of color removal strategies from textile wastewater - Sofía Estévez; Domenica Mosca Angelucci; María Teresa Moreira; M. Concetta Tomei (Science of The Total Environment, 2024)

Sustainable approach for removal of Remazol Red using absorptive polymers: optimization of process performance and sorbent regeneration - D. Mosca Angelucci; V. Stazi; M. C. Tomei (International Journal of Environmental Science and Technology, 2024)

Feasibility of tubing two-phase bioreactors for biological treatment of high toxicity landfill leachate - Domenica Mosca Angelucci; M. Concetta Tomei (Process Safety and Environmental Protection, 2023)

Uptake/release of organic contaminants by microplastics: A critical review of influencing factors, mechanistic modeling, and thermodynamic prediction methods - Domenica Mosca Angelucci; M. Concetta Tomei (Critical Reviews in Environmental Science and Technology, 2022)

The 2020 national seismic hazard model for the United Kingdom - I. Mosca; S. Sargeant; B. Baptie; R. M. W. Musson; T. C. Pharaoh (Bulletin of Earthquake Engineering, 2022)
We present updated seismic hazard maps for the United Kingdom (UK) intended for use with the National Annex for the revised edition of Eurocode 8. The last national maps for the UK were produced by Musson and Sargeant (Eurocode 8 seismic hazard zoning maps for the UK. British Geological Survey Report CR/07/125, United Kingdom, 2007). The updated model uses an up-to-date earthquake catalogue for the British Isles, for which the completeness periods have been reassessed, and a modified source model. The hazard model also incorporates some advances in ground motion modelling since 2007, including host-to-target adjustments for the ground motion models selected in the logic tree. For the first time, the new maps are provided for not only peak ground acceleration (PGA) but also spectral acceleration at 0.2 s (SA 0.2s ) and 1.0 s for 5% damping on rock (time-averaged shear wave velocity for the top 30 m Vs30 ≥ 800 m/s) and four return periods, including 475 and 2475 years. The hazard in most of the UK is generally low and increases slightly in North Wales, the England–Wales border region, and western Scotland. A similar spatial variation is observed for PGA and SA 0.2s but the effects are more pronounced for SA 0.2s . Hazard curves, uniform hazard spectra, and disaggregation analysis are calculated for selected sites. The new hazard maps are compared with the previous 2007 national maps and the 2013 European hazard maps (Woessner et al. in Bull Earthq Eng 13:3553–3596, 2015). There is a slight increase in PGA from the 2007 maps to this work; whereas the hazard in the updated maps is lower than indicated by the European maps.

Coupling proximal sensing, seasonal forecasts and crop modelling to optimize nitrogen variable rate application in durum wheat - F. Morari; V. Zanella; S. Gobbo; M. Bindi; L. Sartori; M. Pasqui; G. Mosca; R. Ferrise (Precision Agriculture, 2021)

Second-tier trio exome sequencing after negative solo clinical exome sequencing: an efficient strategy to increase diagnostic yield and decipher molecular bases in undiagnosed developmental disorders - Frederic Tran Mau-Them; Sebastien Moutton; Caroline Racine; Antonio Vitobello; Ange-Line Bruel; Sophie Nambot; Steven A. Kushner; Femke M. S. de Vrij; Daphné Lehalle; Nolwenn Jean-Marçais; François Lecoquierre; Julian Delanne; et al. (Human Genetics, 2020)

Isoespintanol, a monoterpene isolated from oxandra cf xylopioides, ameliorates the myocardial ischemia-reperfusion injury by AKT/PKCε/eNOS-dependent pathways - Luisa F. González Arbeláez; Alejandro Ciocci Pardo; Juliana C Fantinelli; Benjamín Rojano; Guillermo R Schinella; Susana M Mosca (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Habitat selection and coexistence in small mammals of the southern Andean foothills (Argentina) - Agustina Novillo; M. Fernanda Cuevas; Agustina A Ojeda; Ramiro J. A Ovejero; Mosca Torres; M. Eugenia; Ricardo A Ojeda (Mammal Research, 2017)

Post-aerobic digestion of waste sludge: performance analysis and modelling of nitrogen fate under alternating aeration - M. C. Tomei; N. A. Carozza; D. Mosca Angelucci (International Journal of Environmental Science and Technology, 2016)

The Monviso Massif and the Cottian Alps as Symbols of the Alpine Chain and Geological Heritage in Piemonte, Italy - Franco Rolfo; Piera Benna; Paola Cadoppi; Daniele Castelli; Sergio E. Favero-Longo; Marco Giardino; Gianni Balestro; Elena Belluso; Alessandro Borghi; Fernando Cámara; Roberto Compagnoni; Simona Ferrando; et al. (Geoheritage, 2015)

Metal partitioning in plant–substrate–water compartments under EDDS-assisted phytoextraction of pyrite waste with Brassica carinata A. Braun - T. Vamerali; M. Bandiera; P. Lucchini; G. Mosca (Environmental Science and Pollution Research, 2015)

Evaluation of the measurement uncertainty in automated long-term sampling of PCDD/PCDFs - M. Vicaretti; G. D’Emilia; S. Mosca; E. Guerriero; M. Rotatori (Environmental Science and Pollution Research, 2013)

Long-term automated sampling of PCDD/PCDF flue gas: current status and critical issues - M. Vicaretti; S. Mosca; E. Guerriero; M. Rotatori (Environmental Science and Pollution Research, 2012)

Concentration of organic micropollutants in the atmosphere of Trieste, Italy - S. Mosca; G. N. Torelli; G. Tramontana; E. Guerriero; M. Rotatori; M. Bianchini (Environmental Science and Pollution Research, 2012)

In vivo key role of reactive oxygen species and NHE-1 activation in determining excessive cardiac hypertrophy - Oscar H. Cingolani; Néstor G. Pérez; Irene L. Ennis; María C. Álvarez; Susana M. Mosca; Guillermo R. Schinella; Eduardo M. Escudero; Gloria Cónsole; Horacio E. Cingolani (Pflügers Archiv - European Journal of Physiology, 2011)

Nasal cytology: the “infectious spot”, an expression of a morphological-chromatic biofilm - M. Gelardi; G. Passalacqua; M. L. Fiorella; A. Mosca; N. Quaranta (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Mitochondrial KATP channels participate in the limitation of infarct size by cariporide - Ignacio Pérez Nuñez; Juliana Fantinelli; Luisa F. González Arbeláez; Susana M. Mosca (Naunyn-Schmiedeberg's Archives of Pharmacology, 2011)

Phytotoxicity and metal leaching in EDDS‐assisted phytoextraction from pyrite wastes with Ethiopian mustard and fodder radish - M. Bandiera; G. Mosca; T. Vamerali (Plant Biosystems, 2010)

Studying root distribution with geostatistics - T. Vamerali; M. Guarise; A. Ganis; F. Zanetti; G. Mosca (Plant Biosystems, 2008)

Comparative effects of ischemic pre and postconditioning on ischemia-reperfusion injury in spontaneously hypertensive rats (SHR) - Juliana C. Fantinelli; Susana M. Mosca (Molecular and Cellular Biochemistry, 2007)

Field release of genetically marked Azospirillum brasilense in association with Sorghum bicolor L. - M. Basaglia; S. Casella; U. Peruch; S. Poggiolini; T. Vamerali; G. Mosca; J. Vanderleyden; P. De Troch; M.P. Nuti (Plant and Soil, 2003)

Analysis of root images from auger sampling with a fast procedure: a case of application to sugar beet - T. Vamerali; M. Guarise; A. Ganis; S. Bona; G. Mosca (Plant and Soil, 2003)

A comparison of root characteristics in relation to nutrient and water stress in two maize hybrids - T. Vamerali; M. Saccomani; S. Bona; G. Mosca; M. Guarise; A. Ganis (Plant and Soil, 2003)

Inhibition of mycophenolic acid glucuronidation by niflumic acid in human liver microsomes - M. Vietri; A. Pietrabissa; F. Mosca; G. Pacifici (European Journal of Clinical Pharmacology, 2002)

Mycophenolic acid glucuronidation and its inhibition by non-steroidal anti-inflammatory drugs in human liver and kidney - M. Vietri; A. Pietrabissa; F. Mosca; G.M. Pacifici (European Journal of Clinical Pharmacology, 2000)

Differential inhibition of hepatic and duodenal sulfation of (−)-salbutamol and minoxidil by mefenamic acid - M. Vietri; A. Pietrabissa; R. Spisni; F. Mosca; G. M. Pacifici (European Journal of Clinical Pharmacology, 2000)

Comparison of the protective effects of ischemic preconditioning and the Na + /H + exchanger blockade - Susana M. Mosca; Horacio E. Cingolani (Naunyn-Schmiedeberg's Archives of Pharmacology, 2000)

Inhibition of human liver phenol sulfotransferase by nonsteroidal anti-inflammatory drugs - M. Vietri; C. De Santi; A. Pietrabissa; F. Mosca; G. M. Pacifici (European Journal of Clinical Pharmacology, 2000)

Is stunning prevented by ischemic preconditioning? - Susana M. Mosca; Ricardo J. Gelpi; Jose Milei; Graciela Fernández Alonso; Horacio E. Cingolani (Molecular and Cellular Biochemistry, 1998)

Catechol- O -methyltransferase: variation in enzyme activity and inhibition by entacapone and tolcapone - C. De Santi; P. C. Giulianotti; A. Pietrabissa; F. Mosca; G. M. Pacifici (European Journal of Clinical Pharmacology, 1998)